Toward an ethics and etiquette for electronic mail - Shapiro, Norman Zalmon, 1932-; Anderson, Robert H. (Robert Helms), 1939-; Rand Corporation; National Science Foundation (U.S.) (Santa Monica, CA : RAND, 1985)
This report discusses some important general attributes of electronic mail and message systems, and the effects of those attributes on the quality and appropriateness of communication. The authors discuss the "etiquette" of sending and receiving electronic mail, drawing on personal observation of inappropriate or counterproductive uses of these systems. By presenting some initial guidelines, the authors attempt to accelerate the process by which social customs and behavior appropriate to electronic mail become established, and thereby to accelerate the effective use of such systems.
"July 1985."
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Electronic mail systems; Ethics